Torque Load Analysis on Rear Axle Shaft Material AISI 4340 Normalized - FA Nurmansyah; L Edahwati; RD Issafira; W Saputro; AK Faizin; TP Sari; WD Lestari; N Adyono (BIOMEJ, 2022)
The choice of rear axle shaft material on the car needs to be considered because this component affects the performance of the car. This component material is also very necessary, the selection of components used is AISI 4340 Steel Normalized, where this material contains Nickel, Chrom, and Molybden with the characteristics of the AISI 4340 Steel Normalized material is a steel material that has high hardness properties, can accept great pressure and force and not easy to deform. The method used is the Finite Element Method (FEM), this method uses a meshing size of 5 mm, to get more accurate results. Simulation results from rear axle shaft AISI 4340 Steel Normalized to determine the value of stress, strain, and safety factor from load variations of 1200 Nm, 1400 Nm, 1600 Nm, and 2000. The highest maximum stress value occurs at 2000 Nm torque load of 5.586 x 108 Nm. The highest maximum strain value occurs at a torque load of 2000 Nm of 5.034 x 103. The safest value of the safety factor is 2.1 at a torque load of 1200 Nm. The torque load value is directly proportional to the stress and strain values ​​obtained, because the greater the torque load value, the greater the stress and strain values ​​obtained.